Study on knowledge on the biodiversity of fauna by elementary school children in three communities of the Laguna de Terminos Protected Natural Area, Campeche, Mexico - Trejo, Jenner Rodas; Ocampo-González, Paola; Rau-Acuña, Jaime (Acta Universitaria, 2020)
Drawing has been used as a tool for analyzing children's knowledge of their natural environment. The goal of this study was to analyze the knowledge of elementary school children about the faunistic diversity in three different communities of the Natural Protected Area Laguna de Terminos, using drawing as an exploratory tool. Drawings were analyzed with the content analysis technique, grouping the graphic elements into five categories: animals, terrestrial, aquatic, aerial and anthropic elements. A total of 101 drawings were analyzed, identifying 648 animals of 83 species: 35 mammals, 18 birds, 13 reptiles, 11 fish, four invertebrates, and two amphibians. Most of the elements were represented in jungle and river environments (> 90%). Species with which environmental education activities were carried out, such as crocodiles, manatees, and turtles, were the most represented in the drawings. As a conclusion, it was found that there was a relationship and broad knowledge of children towards the ecosystem.